An Experiential Online Learning Module on Genetics and Genomics for Multidisciplinary Undergraduate Students - Musa, Marahaini; Sulong, Sarina; Mohd Yunus, Nazihah; Annuar, Aziati Azwari; Abdul Aziz, Ahmad Aizat; Zakaria, Wan Nur Amalina; Alwi, Zilfalil; Hussin, Mohd Zaki; Das, Kumitaa Theva; Mohd Nawi, Siti Nurbaya (Education in Medicine Journal, 2026)
Teaching genetics and genomics to multidisciplinary undergraduate students presents challenges due to their varied academic backgrounds, particularly among non-science majors. To address this, YOUnique: From Genes to Gen (Genomics) was developed as an interactive online module introducing fundamental concepts through experiential learning. This module was delivered during the Live Inclusive Fulfilling Experience (LIFE) Programme, a two-week online summer programme offered by Universiti Sains Malaysia (USM). The YOUnique Genomics module aims to build scientific understanding, encourage ethical reflection on emerging genomic technologies, such as gene editing and precision medicine, and foster empathy towards individuals with genetic conditions. It integrates multimedia content, facilitator-led sessions, group discussions and hands-on activities exploring heredity, gene–environment interactions, epigenetics, and ageing. Student feedback indicated strong satisfaction with the module. Most participants strongly agreed that the module was useful, well organised and level appropriate, with activities described as enjoyable (96.1%) and facilitators praised for being knowledgeable, and engaging. Learners found the module relevant to their lives (98.1%) and appreciated the interdisciplinary exposure. Despite some participation barriers, such as Internet issues and personal commitments, students reported enhanced understanding of genetics, and genomics. Word cloud analysis further indicated an understanding of core genetic concepts alongside awareness of real-world applications and ethical issues. The YOUnique Genomics module demonstrates a dynamic, inclusive approach to genetics education across disciplines.